2019
DOI: 10.1177/1539449219860583
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review of Self-Advocacy Education Interventions to Improve Care

Abstract: Self-advocacy is a client’s ability to represent one’s interests when managing disease or disability. Self-advocacy may increase one’s ability to seek, evaluate, and use information to promote health, yet little is known about the role of occupational therapy in promoting self-advocacy. This scoping review aims to identify interventions within occupational therapists’ scope of practice to improve self-advocacy. A literature search was conducted through Academic Search Complete to identify interventions within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…This corresponds with previous literature on LVS delivery [ 25 , 50 ] and implies that patients in need of LVS, but who lack self-advocacy skills are especially at risk of not being referred to LVS. Research in other patient populations suggests that self-advocacy is a teachable skill that contributes to an individualized care trajectory that fits patients’ needs, preferences and values [ 51 , 52 ]. Furthermore, communication aids for patients in medical consultations, for example Question Prompt Lists, may help patients to express their needs and enhance patient participation and information provision [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds with previous literature on LVS delivery [ 25 , 50 ] and implies that patients in need of LVS, but who lack self-advocacy skills are especially at risk of not being referred to LVS. Research in other patient populations suggests that self-advocacy is a teachable skill that contributes to an individualized care trajectory that fits patients’ needs, preferences and values [ 51 , 52 ]. Furthermore, communication aids for patients in medical consultations, for example Question Prompt Lists, may help patients to express their needs and enhance patient participation and information provision [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The similarity of actions used in both age groups can reflect these children and adolescents’ ability to act on, manage, and self-advocate their needs, regardless of their age. Self-advocacy is assertiveness and willingness to represent one’s own interests in making life decisions when managing a disease or disability [ 23 , 37 ]. It involves knowing one’s abilities and needs to recognize problems and ways to address them, being prepared to fulfill these needs and solve problems, communicating with others to solve problems and fulfill needs, and initiating change, including negotiating with others.…”
Section: Discussionmentioning
confidence: 99%
“…The studies found that communication (i.e., how the child feels when speaking about celiac disease) scored highest compared to other health-related quality-of-life components [ 39 , 40 ]. The ability to effectively function in different challenging and complex situations and sufficient self-advocacy skills are imperative for the transitional process of gaining independence from childhood through adolescence and finally to adulthood [ 21 , 37 ]. Furthermore, developing self-advocacy at younger ages to facilitate smoother transitions is significant [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of health care, selfadvocacy is characterized by assertiveness and a willingness to represent one's own interests when managing a disease or disability; it is a learnable behavior that includes accessing relevant information and conveying personal preferences to health care providers. 70 Enabled by knowledge of self and rights, 71 self-advocacy can be improved by enhancing skills in communication, information seeking, problem solving, and securing support 72 that positively impacts health and quality of life. 73 Developing interventions to improve the self-advocacy of women with physical disabilities has the potential to empower them to address stigma and bias and other barriers in productive and self-affirming ways.…”
Section: Discussionmentioning
confidence: 99%